2019
DOI: 10.1590/fst.00718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of leaves used in infusion preparation grown in northeastern Brazil by chemometric methods based on their multi-elemental composition

Abstract: On many places of the world, medicinal plants represent the only form of treatment for various diseases. This work aimed to determine and correlate minerals of infusions and leaves of medicinal plants grown in Northeastern Brazil. Principal component and hierarchical cluster analysis and Pearson correlation were performed. The higher content of Na was for Ocimum basilicum L. (94.3 mg/100g) and Datura stramonium L. (91.6 mg/100g). The plants examined had low levels of K in infusions. All samples contain Mg at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The principal component analysis (PCA) showed that the cumulative variance contribution rate of the first three principal components reached 88.97% (see Table 4), which indicated that these three principal components could accurately and objectively reflect the similarity between samples, so a total of three principal components were extracted (Nascimento et al 2020;Fernandes et al. 2019).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The principal component analysis (PCA) showed that the cumulative variance contribution rate of the first three principal components reached 88.97% (see Table 4), which indicated that these three principal components could accurately and objectively reflect the similarity between samples, so a total of three principal components were extracted (Nascimento et al 2020;Fernandes et al. 2019).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Food quality is related to its content and type of minerals that contribute to taste, appearance, texture and stability, as well as its nutritional value (Fernandes et al, 2019;Nascimento et al, 2020). However, minerals in fruit are affected by environmental factors (Hernández Suárez et al, 2007;Watanabe et al, 2015).…”
Section: Physical and Chemical Properties Of Samplesmentioning
confidence: 99%
“…Principal component analysis is a statistical technique for the reduction of input data dimension and is largely used for feature extraction. It captures the relevant information in a set of input data providing a lower dimension (Fernandes et al, 2019;Nascimento et al, 2020). For improved visualization of the data, PCA was performed to distinguish aroma attributes of 10 shrimp during the hot-air-drying process (Figure 3b).…”
Section: Classification Of Aroma Attributes Of Shrimp During the Hot-airdrying Process Using Pcamentioning
confidence: 99%